Tecnificación del sistema municipal de estacionamiento rotativo tarifado (SIMERT) de la ciudad de Loja, módulo conectividad de la red de datos del Simert utilizando la tecnología GPRS. - Calle Loja, César Danilo (2014)
This research work has been developed in order to do the network connectivity data from the Municipal Parking Rotary Tariffed System (SIMERT) of Loja Canton using GPRS technology; whose purpose is to improve the implementation of the processes that staff of SIMERT carries out daily with the recording of the parking, which allow the appropriate organization and reliability of information. For the development of this research process; methods, techniques were used, and an appropriate methodology was created, beginning with requirements analysis, design, implementation and results measurement, which has let us to fulfill the activities of each one of the phases in an organized way, and to determine the existing problems to give an appropriate solution. Resulting in the implementation of the client-server architecture to perform the network connectivity data SIMERT, through the implementation of a server and the creation sockets, application named "SERVER-SIMERT" ensuring communication security for sending and receiving information from the records of vehicular parking SIMERT; using GPRS technology under the TCP / IP protocol, addressing IP and using ServerSockets class within the application. The server will be a Linux distribution with Ubuntu Server Lucid Lynx 10.04 operating system under the free platform LAMP, which will be configured properly to work as a mail server, web server, data base and application server, using the Mysql database. 5.5.2., The Phpmyadmin v. 5.1.72, Postfix v. 2.7 for the postal service and apache 2.4.2. For the creation of the sockets application named "SERVER-SIMERT" it was used Java programming language under the IDE NetBeans 8.0 virtual platform, the connector database java-5.1.6-bin.jar and libraries Jasypt 1.9.1, Commons-dbcp-1.4 and Commons-pool-1.6. Thus fulfilling each of the goals set at the beginning of the project, which are described in detail in the discussion .